2010
DOI: 10.1021/je100041x
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Data for Optimization of Preparation of Activated Carbon from an Economically Viable Material

Abstract: Activated carbon has been a fascinating material, especially for the removal of different pollutant species from gaseous and aqueous phases. Activated carbons can be prepared from a variety of cellulosic materials. This study is an effort to investigate the characteristics of activated carbon prepared from an agricultural waste material, coconut coir. The surface area and porosity of the activated carbon were determined by nitrogen adsorption isotherms at 77 K. The pore size distribution was determined by a N2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 13 publications
0
11
0
1
Order By: Relevance
“…That means that the organic C of the modified hydrochars would be amorphous. In addition, previous research found the existence of an amorphous C in the activated carbon prepared from coconut coir (Sharma and Gode 2010). Generally, amorphous materials as adsorbents would be better due to their high specific surface area and more active sites on their surfaces (Tchomgui-Kamga et al 2010).…”
Section: Xrd Analysismentioning
confidence: 96%
“…That means that the organic C of the modified hydrochars would be amorphous. In addition, previous research found the existence of an amorphous C in the activated carbon prepared from coconut coir (Sharma and Gode 2010). Generally, amorphous materials as adsorbents would be better due to their high specific surface area and more active sites on their surfaces (Tchomgui-Kamga et al 2010).…”
Section: Xrd Analysismentioning
confidence: 96%
“…[3,4]. The materials used in these processes include rice husk [5], activated carbon [6], orange peel [7], neem leaf [8], red mud [9], bagasse fly ash [10], sawdust [11], conducting polymers [12], etc.…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon has been a material of choice for several pollutants when the removal process is adsorption-based [6]. Carbon-based materials are very well known as adsorbents for dyes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The electroactive nature or the switching properties of PPy Fenton's reagent adsorption [12] Photochemical oxidation [13] Cucurbituril [14] Electrochemical [15] Activated carbon [16] Silica gel [17] Membrane technologies [18] Ion exchange [19] Sawdust (current study) have been utilized as the basis of most proposed applications such as sensors, separation devices, rechargeable batteries, anticorrosion and controlled drug-release [20][21][22][23][24]. Nearly all of the previously reported applications of these conjugated conducting electroactive polymers (e.g.…”
Section: Introductionmentioning
confidence: 99%